Pengaruh Supervisi dan Beban Kerja Terhadap Disiplin Kerja Pegawai BAPPEDA LITBANG Kabupaten OKU Selatan - Indah Herfina Sari; Rosmala Dewi (Fakultas Ekonomi dan Bisnis Universitas Baturaja, 2020)
The purpose of this study was to determine the influence of supervision and workload on the discipline of Bappeda Staff in South OKU Regency. Based on the results of data analysis by researcher and the discussion that has been done, it can be concluded that there is an influence of supervision and workload on work discipline both partially and simultaneously Bappeda Litbang employees in South OKU Regency. The results of the coefficient of determination (R2) is 0.942 then the amount of contribution between supervision and workload on work discipline obtained a contribution of 94.2%, while the remaining 5.8% is influenced by other variables not examined in this study such as objectives and abilities, role models leader, remuneration, justice, inherent supervision (waskat), sanctions, assertiveness, and human relations (Hasibuan (2017: 192))